Endothelial function status in hypogonadal men - I. A. Khripun; S. V. Vorobyev (Сахарный диабет)
Background: Type 2 diabetes mellitus (T2DM) and hypogonadism are mutually aggravating diseases associated with the development and progression of cardiovascular pathology. The status of endothelial function in men with T2DM and hypogonadism hasn’t been studied.Aims: To assess the effect of hypogonadism on endothelial function in men with T2DM.Materials and methods: Patients underwent clinical studies, assessment of carbohydrate and lipid metabolism, the content of sex hormones (total testosterone (T), sex hormones binding globulin, free T, luteinizing hormone) and markers of endothelial function (nitric oxide (NO), endothelial nitric oxide synthase type 3 (eNOS3), endothelin, adhesion molecules ICAM-1, VCAM-1, p- and e-selectins, cadherin), ultrasound examinations of endothelium-dependent vasodilation (EDVD) of the brachial artery (BA) and carotid arteries with an assessment of the thickness of intima-media complex (TIM) were performed.Results: The study included 276 men with T2DM (age 54.0[49;60] years), who were divided into 2 groups: 1–124 patients with hypogonadism; 2–152 eugonadal patients. Reduction of the endothelial vasomotor function was detected in 32.4% of patients in the 2st group and in 55.3% of the 1nd group (χ2=6.1; p=0.01), which was associated with a decrease in EDVD by 29.8 % (p<0.001) and an increase in the time of development of maximal BA vasodilation by 30 seconds in patients with hypogonadism (p<0.001). The TIM of the carotid arteries was 10% more in group 1 compared with group 2 (p=0.03). The level of NO in the 1st group was reduced by 1.6 times (p=0.001), eNOS3–by 1.5 times (p=0.038) compared with the 2nd group. The concentrations of adhesion molecules were higher in group 1 compared to group 2: VCAM-1 by 32.5% (p<0.001), ICAM-1 by 43.5% (p<0.001), p-selectin–by 19.3% (p=0.004), cadherin–6 times (p<0.001).Conclusion: Hypogonadism in men with T2DM is associated with the development of endothelial dysfunction, which manifests in a weakening of the EDVD and a slowdown in its development, as well as disturbances of the secretory activity of endothelium–a decrease in NO synthesis and activation of the adhesion molecules expression, which can be regarded as an universal pathogenetic mechanism of the development of cardiovascular diseases in combination of T deficiency and T2DM.